Estimating the Direct Medical Costs and Productivity Loss of Outpatient Chlamydia and Gonorrhea Treatment. Issue 2 (February 2021) - Kumar, Sagar; Chesson, Harrell; Gift, Thomas L.
Abstract : Abstract: We used 2016–2017 administrative claims data to calculate the direct medical cost and productivity loss per diagnosed case of chlamydia and gonorrhea treatment. In 2018 US dollars, the direct cost per diagnosed case was 151 for chlamydia (n = 9180) and 85 for gonorrhea (n = 3048); productivity loss was 206 (n = 31) and 246 (n = 7), respectively, among those missing work seeking care. Abstract : Using administrative claims data, we estimated medical costs to be 151 and 85 per case of chlamydia and gonorrhea, respectively. Among those missing work, productivity losses per case were higher.Supplemental digital content is available in the text.